Direct synthesis of layered double hydroxide nanosheets for efficient siRNA delivery. Issue 98 (6th October 2016) - Li, L.; Gu, Z.; Gu, W. Y.; Xu, Z. P.
Abstract : In this paper, we have developed a simple yet efficient method to prepare stable single-sheet MgAl-layered double hydroxide (MA-NS) suspensions without using organic solvents or surfactants. Abstract : In this paper, we have developed a simple yet efficient method to prepare stable single-sheet MgAl-layered double hydroxide (MA-NS) suspensions without using organic solvents or surfactants. This green approach involves a fast co-precipitation with hydrothermal treatment. The average hydrodynamic diameter of mono-disperse fully-delaminated LDH nanosheets can be precisely tailored in the range of 25–300 nm. The reproducibility of making identical suspensions under identical conditions has been confirmed and the method has also been successfully applied to prepare stable and single-layered LDH nanosheet suspensions containing various transition metal ions such as Ni 2+, Fe 2+, Fe 3+ and Co 2+ in the single hydroxide layer. MgAl–LDH nanosheets (MA-NSs) with various sizes do not exhibit any acute cytotoxicity at concentrations up to 400 μg mL −1 as assayed by MTT. The cellular uptake and cell viability data have demonstrated MA-NSs can efficiently load and deliver small interfering RNA (siRNA) into osteosarcoma (U2OS) cancer cells, and significantly inhibit their growth. Thus, MA-NSs have great potential as an effective cellular delivery system for siRNA therapy, in addition to their conventional applications in coatings, catalysis, composites and adsorption.